STUDI PERSEPSI MASYARAKAT SETEMPAT TERHADAP DAYA DUKUNG HABITUASI KOTA PALU PASCA BENCANA TAHUN 2018 - Kokalinso, Febrianti Margaretha; Rogi, Octavianus H. A.; Siregar, Frits O. P. (SPASIAL, 2021)
Disaster is an event or series of events that threaten and disrupt people's lives caused by both natural and/or non-natural factors including human actions, resulting in human casualties, environmental damage, property losses and psychological impacts. The traumatic experience as a result of the disaster can basically change the perception of the local community regarding the existence of their place of residence where the disaster has occurred. The analytical method used is the Likert scale, simple description, Spearman rank test and chi square test. Liker scale analysis is used for manual calculations using a formula to measure the opinions of each respondent, simple description analysis makes conclusions from the results of the questionnaire. Meanwhile, the chi square test and the rank of separman are used to find out how far the consistency of people's answer choices is related to perceptions, preferences and affection. The results of the study show that they can still survive or habituated in the city of Palu as long as the community can support each other, then they still choose to stay in the city of Palu by having the ability to seek mitigation properly and correctly.Â Keywords:Public perception, Likert scale, Spearman rank test and chi square test.